Duy trì đội ngũ giảng viên ở các trường đại học công lập tự chủ tài chính khu vực miền Bắc - Nguyễn Danh , Nam; Uông Thị Ngọc, Lan (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
The study aims is to determine the impact of job satisfaction, organizational commitment, and work motivation on faculty retention at self-financed public universities in Northern Vietnam. The quantitative approach was employed to evaluate the impact of these factors on faculty retention. A structured questionnaire was administered online to obtain information on lecturers. The SPSS 26 was used to produce the demographic information of lecturers and the SmartPLS 3.0 version was used to process the SEM. The research results pointed out that job satisfaction, organizational commitment, and work motivation have positive impacts on faculty retention. Additionally, job satisfaction has an active correlation with organizational commitment, and work motivation of lecturers. Based on the research results, several management implications are recommended to enhance the effectiveness of faculty retention at self-financed public universities in the future.
Keywords: Job satisfaction; Organizational commitment; Work motivation; Faculty retention